Integrated inductors and transformers : characterization, design, and modeling for RF and MM-wave applications - Ragonese, Egidio (Boca Raton, FL : Auerbach Publications, 2010)
'Passive inductive components have experienced an extraordinary growth in RF ICs. They are widely employed to improve performance, reduce fabrication costs and increase integration levels of both the RX and TX parts of the RF front-end. Knowledge of basic concepts concerning design, fabrication, and modeling of monolithic inductors and transformers has become an essential prerequisite for process engineers and circuit designers. In this book, monolithic passive components are discussed to provide a complete overview on fabrication technology, design and optimization techniques, and modeling. Equal emphasis is given to technological aspects and circuit-oriented applications'--
Includes bibliographical references and index.
Keywords: Radio frequency integrated circuits; Electric inductors; Electric transformers